Sensibilisation aux acariens chez les enfants suivis pour allergie respiratoire en milieu tropical africain à Cotonou, Bénin - AGODOKPESSI, DEGLA DE LUXE GILDAS; SAGBO, GODONOU GRATIEN; BIGOT, CÉDRIC EGNONWA PARFAIT; HOUNTOHOTEGBE, Tatiana; Dossou-Yovo, S; DJOGBESSI, D; BIGOT, KOFFI ANDRÉ (My University, 2018)
Summary Introduction. - ln tropical Africa, allergies are not weil documented. The objective of this work was to evaluate, by two methods, the sensitization to mites in children iollowed for respiratory ,jllergy. Methods. - Skin prick-test and IgE assay by REAST test with 3 mites: Dermatophagoides pteronyssinus (D. pteronyssinus) , Dermatophagoides {arinae (O. {arinae) and Blomia trop/colis (B. trop/calis) were carried out in children from 3 to 15 years followed up for asthma and/or allergic rhinitis. The positive results of the two tests were compared. Results. - Of the 130 (100%) children included, ail eligible for the assay, 119 (91.5%) had the prick-test. The mean age and sex ratio (MlF) were 7 ± 1 year, and 1.6. The association of rhinitis and asthma was the most frequent and found in 66 (55.6%). The sensitivity frequencies for the prick-test and assay were respectively 79% versus 36.1% for B. tropicalis, 71.4% versus 33.4% for D. pteronyssinus and 38.7% versus 37.8% for D. {arinae. A moderate correlation between mean papule diameter and mean IgE concentration was observed. Conclusion. - ln African tropical environments, dust mite sensitization in children followed for respiratory allergy is frequent, with the order of frequency being: B. tropicalis, D. pteronyss;nus, and D. {arinae. The prick-test had better sensitivity than the assay for its evaluation.
Keywords: acariens; allergie respiratoire